HUBUNGAN PENERIMAAN ORANGTUA DENGAN DEPRESI PADA SISWA SMP NEGERI 1 MUNTILAN - , MELITA PUSPITA SARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Adolescence is a period of development of self-identity (identity), and became the foundation for adulthood period. Many factors affect the psychological development of adolescent, such as family environment and relationships with parents. As we know that the role of a parent is a \" first school \" for the children include to teach their children on how to act and resolve the problem. Problems faced can cause depression in adolescent. Based on the National Alliance on Mental Illness (NAMI), for about 2% of school-aged children and about 8% of adolescents meet the criteria for major depression. Objective: The objective of this study was to determine whether there is a relationship between parental acceptance and depression of students of SMP Negeri 1 Muntilan. Method: This study is a descriptive analytic correlational with cross-sectional approach, with quantitative method. This study needs 112 students using Parental Acceptance-Rejection Quistionnaire (PARQ) to measure parental acceptance (father and mother), and Children's Depression Inventory (CDI) to measure childrenâs depression. Results: There is a positive correlation between parental acceptance and child's depression. Father and mother acceptance significantly affect the child depression with p = 0.000 acceptance mother (<0.05 ), and the p-value = 0.018 father acceptance (<0.05 ). Conclusion: There is a significant relationship between parental acceptance of the child's level of depression.